Church discourse on HIV / AIDS: a responsible response to a disaster? - Pillay, Miranda N. (Scriptura: Journal for Contextual Hermeneutics in Southern Africa, 2003)
The HIV / AIDS epidemic continues to evolve and has now reached pandemic proportions in South Africa and other developing countries throughout the world. HIV / AIDS presents a challenge to the well-being of individuals and to the public health of proportions unprecedented in modern history. While the challenge is scientific and medical, it is also psychological, legal, economic, social, ethical and theological. It is no longer a question of "why" the church should respond but rather "how" the church ought to respond. When the churches' response to the HIV / AIDS pandemic is analysed within the framework of the disaster management continuum, one gains a schematic perspective of the current responses as well the gaps in such responses.
Free